Pericyte Antigens in Perivascular Soft Tissue Tumors. (December 2015) - Shen, Jia; Shrestha, Swati; Yen, Yu-Hsin; Asatrian, Greg; Mravic, Marco; Soo, Chia; Ting, Kang; Dry, Sarah M.; Peault, Bruno; James, Aaron W.
Introduction . Perivascular soft tissue tumors are relatively uncommon neoplasms of unclear line of differentiation, although most are presumed to originate from pericytes or modified perivascular cells. Among these, glomus tumor, myopericytoma, and angioleiomyoma share a spectrum of histologic findings and a perivascular growth pattern. In contrast, solitary fibrous tumor (previously termed hemangiopericytoma) was once hypothesized to have pericytic differentiation. Methods . Here, we systematically examine pericyte immunohistochemical markers among glomus tumor (including malignant glomus tumor), myopericytoma, angioleiomyoma, and solitary fibrous tumor. Immunohistochemical staining and semiquantification was performed using well-defined pericyte antigens, including αSMA, CD146, and PDGFRβ. Results . Glomus tumor and myopericytoma demonstrate diffuse staining for all pericyte markers, including immunohistochemical reactivity for αSMA, CD146, and PDGFRβ. Malignant glomus tumors all showed some degree of pericyte marker immunoreactivity, although it was significantly reduced. Angioleiomyoma shared a similar αSMA + CD146 + PDGFRβ+ immunophenotype; however, this was predominantly seen in the areas of perivascular tumor growth. Solitary fibrous tumors showed patchy PDGFRβ immunoreactivity only. Discussion . In summary, pericyte marker expression is a ubiquitous finding in glomus tumor, myopericytoma, and angioleiomyoma. Malignant glomus tumor shows a comparative reduction in pericyte marker expression, which may represent partial loss of pericytic differentiation. Pericyte markers are essentially not seen in solitary fibrous tumor. The combination of αSMA, CD146, and PDGFRβ immunohistochemical stainings may be of utility for the evaluation of pericytic differentiation in soft tissue tumors.